Shocking Mother Russia : Democratization, Social Rights, and Pension Reform in Russia, 1990-2001. - Chandler, Andrea (University of Toronto Press, 2014)
Shocking Mother Russia places the Russian experience in comparative perspective, and suggests lessons for pension reform derived from analysis of the Russian case.